PO167 Adrenergic signalling and congenital myasthenic syndromes. (1st December 2017) - McMacken, Grace; Spendiff, Sally; Howarth, Rachel; Cox, Dan; Slater, Clarke; Roos, Andreas; Whittaker, Roger; Lochmuller, Hanns
Abstract : Background: Therapies which alter neuromuscular transmission remain poorly understood, both in terms of their mechanism of action and their varying efficacy in the diverse range human pathologies in which the neuromuscular junction (NMJ) is implicated. In particular, therapies acting on the sympathetic nervous system lead to unexplained improvement in subsets of congenital myasthenic syndromes (CMS), a group of disorders caused by mutations affecting components of the NMJ. Aims: To explore the mode of action of sympathomimetics on NMJ development and structure, and identify principle routes by which adrenergic modulation exerts a physiological effect. Methods: We are studying the effect of sympathomimetics in zebrafish CMS models and several CMS mouse models. Further evidence for the effect of these drugs on neuromuscular transmission will be sought in CMS patients, using serial neurophysiological assessment. Results: Our results demonstrate alleviation of the phenotype and NMJ pathology of zebrafish with morpholino mediated knockdown of Dok-7 and MuSK, indicating a role for adrenergic signalling in acetylcholine receptor prepattern and axon guidance. Mouse models of CMS due to mutations in DOK7 (Beeson laboratory, Oxford), AGRN (Burgess laboratory, Jackson) and COLQ (Legay laboratory, Paris) have been bred and characterised, and analysis of the effects of salbutamol is ongoing.